PENGARUH MEDIA SOSIAL INSTAGRAM @halodoc TERHADAP PEMENUHAN KEBUTUHAN INFORMASI KESEHATAN FOLLOWERS - Desi Aspika Rossza; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The development of internet-based media is also used by the health world to spread information about health or called E-Health. Instagram social media has become one of the media chosen to spread health information. At the moment many accounts on social media Instagram have been created specifically to disseminate health information, one of which is @halodoc. The existence of the @halodoc Instagram account makes it easy for followers to get the health information they need. This study uses the theory of uses and gratification with the aim of the study to analyze how much influence social media on Instagram @halodoc on fulfillinghealth information needs followers'.The method used in this research is quantitative explanatory random sampling technique and the number of samples is 400 respondents. Data collection techniques in this study used a questionnaire. To find out how much influence the two variables have, the writer uses simple linear regression analysis. Furthermore, data testing was performed using the SPSSprogram for windows version 21.Based on the results of a simple linear regression, the regression coefficient values obtained in this study were Y = 12.495 + 0.475 X with a significance level of 0.000. The significance level is smaller than α = 0.05, which means Ho rejected and Ha accepted, with the statement that there is the influence of social media on the fulfillment instagram @halodoc health information needs followers.The coefficient of determination (R2)in the study of 26.6% which atinya figures show that the influence of social media instagram @halodoc to meet the needs of health information followers. included in the category of weak While the remaining 73.4% is influenced by other variables not included in this study.